Students’ societal mattering as a protective factor against depression and suicidal thoughts - Sheng Yee Wan; Kususanto Ditto Prihadi; Prakrisno Satrio (International Journal of Public Health Science (IJPHS), 2022)
Suicide ideation or suicidal thought has been reported to be one of the major mental wellbeing issues among university students following the increase of the depressive symptoms. The implication of social distancing in the form of lockdown did not help to reduce the aforementioned cases. While we know that reducing depressive symptoms among university students might be almost impossible to be done without any drastic change to the educational system, we would like to investigate whether the sense of mattering to the university might moderate the development of suicide ideation when the students have developed depressive symptoms. We recruited 435 university students and had they voluntarily responded to the Beck’s depression inventory, satisfaction with life scale, societal mattering scale, and the suicidal ideation attributes scale. The data was analyzed by bias-free bootstrap analysis with 5,000 samplings and 95% confidence interval in PROCESS Macro model 59 and model 1, and the results reported that high university mattering levels might moderate the link between depression symptoms and suicide ideation through life satisfaction. In other words, in the situation where the students were locked-down, the chance of develop depression and the idea to end their own life tend to be higher. However, the more they believe that they matter to their university as a society, the less they will develop depression symptoms and the suicide ideation.